Economic Reforms and Health Indicators in Nigeria - Saheed O. Olayiwola; Francis O. Adeyemi; Musibau O. Ogundeji (Journal of Developing Economies, 2026)
Objective: The economic reform programmes have failed to yield the anticipated improvements in health outcomes in Nigeria, due to deteriorating health outcomes. This study empirically examines the effect of economic reforms on health indicators in Nigeria. Design/Methods/Approach: The study employed descriptive analysis and Autoregressive Distributed Lag estimation technique (ARDL) with time series data extracted from the World development reports. Findings: The trend analysis reflects unimpressive impacts of economic reforms on the health indicators. The ARDL results show a mix of improvement and deterioration in the health indicators. A 10% increase in domestic health expenditure increases Immunization and life expectancy by 6.3%, and 0.1% in the long run, and 3.8%, and 0.1% in the short run. It decreases undernourishment by 3.2%, reduces stunting by 0.4% and infant mortality by 0.03% in the short run. A 10% increase in Out-of-pocket expenditure increased undernourishment by 5.9%, reduced prenatal care by 9.6%, stunting by 3.3%, and life expectancy by 0.4% in the long run. A 10% change due to social sector reform increased immunization by 1.9%, prenatal care by 0.9%, increased HIV/AIDS infections by 0.1%. A 10% change due to trade reform increased the immunization by 3.9%, HIV/AIDS infection by 0.5%, in the short run. A 10% change in domestic financial reform increased Immunization by 4.6%, HIV/AIDS infection by 1.9%, reduced prenatal care by 1.5%, and undernourishment by 2.3%. These results implied that economic reform alone cannot provide the expected improved outcomes in health indicators. Originality/Value: This study extends empirical investigation to cover social sector reform, domestic financial sector reform, trade reform and SAP, NEEDS, and transformation agenda. Practical/Policy implication: Actions on economic transformation and health indices must address distortions that inhibit the realization of the economic reform agenda. Government should be more intentional in curtailing the distortions that impede the growth process and carefully choose policy variables for economic reform and health outcomes.